The Nature off Traditional Minahasan Marriage in the Perspective of Protestant Christianity - Brendah Veldrin Pua; Gunardi Lie (Eduvest - Journal of Universal Studies, 2024)
This study examines the nature of Minahasa traditional marriage in the perspective of Protestant Christian beliefs, describing the acculturation process between local traditions and religious teachings. The study shows that Minahasa traditional marriage has undergone significant transformation with the inclusion of Protestant Christian influences, creating a unique synthesis between traditional and spiritual values. The role of family and community in marriage remains significant but has undergone reinterpretation, encompassing aspects of spiritual and material support. Traditional concepts such as 'mapalus' (gotong royong) took on a new dimension in the church context. The responsibilities of husband and wife have also shifted towards a more egalitarian direction, although some traditional aspects remain.In conclusion, Minahasa traditional marriage in a Protestant Christian perspective reflects the harmonization between cultural heritage and religious beliefs, showing how tradition and modernity can go hand in hand. This study provides valuable insights into the dynamics of culture and religion in Indonesia, and highlights the importance of an ongoing dialogue between customary traditions and religious teachings in the context of social change.